Ecological adaptation interpretation of intertidal gastropod communities on hard-substrate habitats in Tomini Bay Waters, Pohuwato Regency - Miftahul Khair Kadim; Khairinissa Septiani Makmur; Nuralim Pasisingi; Faizal Kasim; sandriyanto djunaidi (Universitas Malikussaleh, 2026)
Intertidal gastropod communities on hard-substrate habitats may reflect ecological responses to microhabitat heterogeneity through community structure and spatial distribution patterns. This study aimed to interpret the ecological responses of intertidal gastropod communities in Tomini Bay waters, Pohuwato Regency, through an analysis of community structure and distribution patterns across five stations (KP1–KP5) selected based on the presence of hard substrates, namely dead coral and rocky habitats (including natural rocks and breakwaters). Distribution patterns were analyzed using Morisita’s Index and confirmed by a chi-square (χ²) test. Overall, 74 species from 21 families were identified, with a total of 17,827 individuals. Rocky habitats had higher individual abundance, whereas cumulative species richness was higher in dead-coral habitats. The community showed strong dominance by Planaxis sulcatus, which was associated with low diversity at certain stations, with the highest H′ value recorded at KP4 (2.628) and the lowest at KP5 (0.153), while the highest D value (0.954) was recorded at KP5. Dispersion analysis showed that clumped patterns predominated in both habitats, and the proportion of records with significantly clumped patterns was higher in rocky habitats than in dead-coral habitats. These results indicate that spatial distribution patterns are an important component in the ecological interpretation of intertidal gastropod communities on hard substrates. Keywords: Dispersion Pattern; Gastropoda; Intertidal; Tomini Bay